GAGASAN CONSTITUTIONAL COMPLAINT DALAM PENEGAKAN HAK KONSTITUSIONAL DI INDONESIA - Annisa Sherin Uswatun Erly; Mexsasai Indra; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Constitutional rights are not only limited to written recognition in documents, but there must be real protections that can truly guarantee and protect the basic rights of citizens. A very important problem arises in the effort to protect the constitutional rights of citizens, namely how constitutional violations are not against the enactment of laws or decrees. The facts show that many cases submitted to the Indonesian Constitutional Court are indicated to have violated constitutional rights. Meanwhile, all existing legal remedies that have been taken by the complainant cannot be accepted (niet onvankelijk verklaard) or withdrawn by the complainant before the judicial process is carried out, due to the unavailability of the authority to try the case in the Constitutional Court, even in all judicial institutions in Indonesia. Therefore, a court is needed to accommodate problems related to the constitutional rights of citizens such as Constitutional Complaint.The type of research used in this legal research is the normative juridical method, with a study of legal principles, namely the principle of legal certainty. Research is descriptive in nature, which is a study that aims to make a clear and detailed description of the problem. The data source used is secondary data. The data collection technique in this research is the literature review method after the data is collected and then analyzed to draw conclusions.From the results of research and discussion, it was found that there were cases that did not get legal certainty because they could only be filed in a Constitutional Complaint, in which Indonesia did not yet have an institution that was responsible for Constitutional Complaints. In Indonesia, the legal means that can be taken to file a Constitutional Complaint case to the Constitutional Court in Indonesia is through the judicial review, although it does not always run smoothly. There are only a few cases with Constitutional Complaint content that passed when they were brought to the Constitutional Court through a judicial review mechanism. In practice in Indonesia, even though judicial review has become the authority of the Constitutional Court, this is only limited to the product of the DPR (laws) so that actions (policies) either the government (executive), legislative, or judiciary have the potential to harm the rights of citizens who have already guaranteed by the constitution, especially rights that are fundamental rights have not been properly protected. In a country that adheres to the concept of a democratic state, such as in Indonesia, the constitutional complaint mechanism is very important to regulate.Keywords: Human Rights - Constitutional Complaint